CAMEO : Conservation & Art Material Encyclopedia Online - Museum of Fine Arts, Boston (2000)
[Dt.:] CAMEO ist die Datenbank des Conservation and Collections Management Department am Museum of Fine Arts in Boston. Sie enthält Informationen zu 10.000 historischen und zeitgenössischen Materialien für Restaurierung, Konservierung, Kunst und Architektur. Außerdem enthält die Site ein umfangreiches Verzeichnis mit Institutionen für Konservierung und Restaurierung weltweit. - [Engl.:] CAMEO is a searchable encyclopedia developed at the Conservation and Collections Management Department at the Museum of Fine Arts, Boston. CAMEO contains chemical, physical, visual, and analytical information on over 10,000 historic and contemporary materials used in the conservation, preservation, and production of artistic, architectural, and archaeological materials.